2015
DOI: 10.2527/jas.2014-8400
|View full text |Cite
|
Sign up to set email alerts
|

Equations generated to predict iodine value of pork carcass back, belly, and jowl fat1,2

Abstract: Data from existing literature were used to generate equations to predict finishing pig back, belly, and jowl fat iodine values (IV) and an experiment was conducted to evaluate these equations. The final database included 24, 21, and 29 papers for back, belly, and jowl fat IV, respectively. For experiments that changed dietary fatty acid composition, initial (INT) diets were defined as those fed before the change in diet composition and final (FIN) diets were those fed after. The predictor variables tested were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…A literature review was conducted to compile studies that examined the effects of floor space allowance on ADG, ADFI and G : F of finishing pigs. The literature review and database development used similar techniques as described previously for predicting the effects of net energy on ADG and G : F by Nitikanchana et al (2015) and the effects of dietary composition on pork fat iodine value by Paulk et al (2015). Briefly, the literature search was conducted via the Kansas State University Libraries, utilizing the CABI search engine, and using the keywords 'space requirement' or 'floor space allowance' with 'finishing pig' or 'growing pig.'…”
Section: Methodsmentioning
confidence: 99%
“…A literature review was conducted to compile studies that examined the effects of floor space allowance on ADG, ADFI and G : F of finishing pigs. The literature review and database development used similar techniques as described previously for predicting the effects of net energy on ADG and G : F by Nitikanchana et al (2015) and the effects of dietary composition on pork fat iodine value by Paulk et al (2015). Briefly, the literature search was conducted via the Kansas State University Libraries, utilizing the CABI search engine, and using the keywords 'space requirement' or 'floor space allowance' with 'finishing pig' or 'growing pig.'…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Paulk et al (2015) performed a literature review to create predictive equations for back, belly, and jowl IV based on many different variables such as EFA, ADFI, and initial BW. The current study was used to vali date the predictive equations and they were found to be moderately accurate for estimated backfat IV values, but they overestimate most backfat values, especially for pigs with backfat IV under 65 g/100 g. Belly fat IV was un der predicted for most treatments, with only 34% of the variation explained by the model.…”
Section: Discussionmentioning
confidence: 99%
“…This study was used to validate those equa tions. A portion of the data from this study was reported by Paulk et al (2015) with the remainder being reported herein. This study was conducted to determine the effects of feeding soybean oil, beef tallow, or a blend of the 2, as well as feeding duration, on finishing pig growth perfor mance, carcass characteristics, and IV of belly and jowl fat and backfat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using dietary C18:2 or IVP as a single predictor variable resulted in highly variable PE ranging from 3.43 to 8.36 g/100 g and bias ranging from −5.05 to 5.66 g/100 g. In contrast, Eq. [8], [13], and [16] were developed from a meta-analysis by Paulk et al (2015) and included multiple predictive factors involving diet lipid composition, feeding days, NE content of diets, live growth performance criteria, and carcass composition. Therefore, it is reasonable to expect that adding these additional predictors may improve the prediction of IV because they more broadly account for the variation in dietary energy concentration as well as changes in diet composition that affect the intake and metabolic utilization of dietary lipids by pigs.…”
Section: Prediction Of Iodine Valuementioning
confidence: 99%